A Profile of the Farm Machinery Industry - Drake, Dawn M (Business Expert Press, 2014)
Ebook from IG Library ; The farm machinery industry, though dominated by three large companies, is a complex sector of the global manufacturing economy that encompasses many smaller manufacturers as well. While contributing a small percentage to gross world product, it is vitally important to another key sector of the economy agriculture. Consequently, the recent rise in global crop prices has allowed the industry to be more resilient than other mature manufacturing sectors, like automobiles. The proposed book will provide a concise but comprehensive look at the farm machinery industry: its history, organization, competitors, and the challenges and opportunities the industry faces as a result of regulations, globalization and outside market forces. This will be done as a means of understanding a crucial building block to the success of agriculture's ability to feed the expanding world population.